2008
DOI: 10.1186/cc6869
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory effects of different recruitment maneuvers in acute respiratory distress syndrome

Abstract: Introduction Alveolar derecruitment may occur during low tidal volume ventilation and may be prevented by recruitment maneuvers (RMs). The aim of this study was to compare two RMs in acute respiratory distress syndrome (ARDS) patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 46 publications
2
36
0
3
Order By: Relevance
“…T he aim of recruitment maneuvers (RMs) in acute respiratory distress syndrome (ARDS) and acute lung injury is the reaeration of insufficiently aerated lung regions through an intentional, transient increase in transpulmonary pressure (1)(2)(3). Improving gas exchange and attenuating ventilator-induced lung injury are the major expected benefits through the prevention of repetitive "opening and closing of unstable lung units" (4,5).…”
mentioning
confidence: 99%
“…T he aim of recruitment maneuvers (RMs) in acute respiratory distress syndrome (ARDS) and acute lung injury is the reaeration of insufficiently aerated lung regions through an intentional, transient increase in transpulmonary pressure (1)(2)(3). Improving gas exchange and attenuating ventilator-induced lung injury are the major expected benefits through the prevention of repetitive "opening and closing of unstable lung units" (4,5).…”
mentioning
confidence: 99%
“…Despite a careful fluid management prior to RM to maintain pulse pressure variation below 13% [32], systolic and mean arterial pressures decreased progressively throughout the RM and became significant at 20 and 30 s with a rapid recovery of the basal condition 30 s after the end of the RM. Overall systolic and mean arterial pressures decreased by a median value of 16 [8-28] mmHg and 8 [2][3][4][5][6][7][8][9][10][11][12][13] mmHg, respectively, from the beginning to the end of the RM. Such an impairment may have clinical consequences, especially as arterial pressure underestimates the true effect of the RM on cardiac output [10].…”
Section: Discussionmentioning
confidence: 99%
“…A 10-s sustained inflation RM would have limited the decrease in systolic and mean arterial pressures. Studies comparing hemodynamic parameters before and after the RM reported no hemodynamic compromise, probably because of this transient effect [6,13,34]. In animal models, hemodynamic compromise was constant but differed according to the model used (pneumonia being worse than oleic acid injury or VILI) and the RM performed (40-s sustained inflation RM being worse than incremental PEEP) [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Respiratory effects of different RMs have also been studied. [6] Bacterial translocation from the lungs to the bloodstream has been used as a marker of VILI in a number of experimental…”
mentioning
confidence: 99%